Ustadz Roles in Developing Students' Interpersonal Intelligence at Islamic Boarding Schools: A Case Study Approach - Juli Setio; Munir; Fitri Oviyanti (Journal of Innovation and Research in Primary Education, 2026)
The development of students' interpersonal intelligence represents a critical yet underexplored dimension of Islamic boarding school (pesantren) education, particularly concerning the specific pedagogical mechanisms through which educators facilitate competencies in empathy, prosocial behavior, and self-awareness essential for socially competent graduates. This qualitative case study examined ustadz roles in developing interpersonal intelligence at Pondok Pesantren Darunur Al-Musthafa Palembang through participant observation, in-depth interviews with purposively selected ustadz and students, and documentation analysis. Data were analyzed using Miles and Huberman's interactive model, with validity ensured through source, technique, and time triangulation. Findings reveal that ustadz systematically implement four complementary roles (model, facilitator, mediator, and motivator) across three interpersonal intelligence dimensions: prosocial behavior (sharing, cooperation, helping, honesty, donation), self-awareness (recognizing behavior, identifying strengths/weaknesses, independence, decision-making, expressing thoughts/feelings, self-evaluation), and social communication skills (effective speaking and listening). Development occurs through embodied pedagogy within authentic pesantren community contexts rather than isolated instructional interventions, with unexpected findings revealing effective self-awareness cultivation without formalized reflection programs. Results align with Bandura's social learning theory, Goleman's emotional intelligence framework, and communication competence theory while demonstrating how traditional Islamic educational practices integrate with contemporary developmental psychology principles. The study contributes theoretically by bridging Islamic pedagogical wisdom with modern social-emotional learning frameworks and practically by providing adaptable strategies for holistic interpersonal intelligence development in diverse educational contexts.